Creation and evolution of the tax on financial movements (2021)
In Colombia there are different types of taxes which are determined by the Congress of the Republic and are divided into national or territorial taxes, within national taxes we can find the tax on GMF financial movements, of which in this Written It aims to analyze the current situation of this tax, its evolution, and the reasons for which it was created. In addition, exposing which has been the impact of that tax, where the resources that are obtained from it go and as it is its application.